A Bibliometric Analysis of Chatbot Implementation - Agus, Taufiq; Siti Mujanah; Fianto, Achmad Yanu Alif (International Journal of Economics (IJEC), 2025)
The use of artificial intelligence (AI)-based technology is increasingly widespread. This includes the use of chatbots. Chatbots are used in various sectors including education, health, and technology. This study aims to analyze research related to chatbots in the 2022-2024 period. The research method used is a bibliometric analysis approach. Collection of articles from Google Scholar using Harzing's Publish or Perish software and analysis using VOSviewer software. The word "chatbot" is used as a keyword in the search for the article. The results obtained were 999 relevant publications with 30705 citations and 15352 cites/years discussing chatbots. The results of the analysis show that there are nine main clusters related to chatbots. This includes research on the use of chatbots during the Covid-19 pandemic. This article also provides information on research topics that have not been widely discussed such as GPT, educational chatbots, and medical chatbots. This is expected to be used as a reference by other researchers to discuss this topic in further research.